2020
DOI: 10.1177/0253717620930317
|View full text |Cite
|
Sign up to set email alerts
|

Can Cancer Diagnosis Help in Quitting Tobacco? Barriers and Enablers to Tobacco Cessation Among Head and Neck Cancer Patients from a Tertiary Cancer Center in South india

Abstract: Background: Tobacco use contributes to almost 40% of the cancers in India. Considering the potential threat, many preventive measures have been instigated in the country. However, tobacco cessation for hospitalized cancer patients is an unexplored territory in India. This study aims to understand the quit status and to explore the reasons to quit or continue the use of tobacco after the diagnosis of head and neck cancer (HNC). Methods: HNC patients admitted between February and April 2016 were assessed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…These rates are similar to previous reports,[ 4 ] specifically from India. [ 15 ] The encouraging fact is that >85% of patients have attempted to quit after the diagnosis and show willingness to quit in near future. Although advised routinely in cancer clinics to quit SLT use, a more formal and structured SLT cessation sessions might help them better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are similar to previous reports,[ 4 ] specifically from India. [ 15 ] The encouraging fact is that >85% of patients have attempted to quit after the diagnosis and show willingness to quit in near future. Although advised routinely in cancer clinics to quit SLT use, a more formal and structured SLT cessation sessions might help them better.…”
Section: Discussionmentioning
confidence: 99%
“…Mathew et al . (2020),[ 15 ] a recent study from India, qualitatively identified factors associated with quitting successfully and continued use in patients with HNC. While perceived benefits of quitting and advice from the physicians were reported as reasons to quit, poor coping and nihilistic attitude regarding cancer outcomes were reported as reasons for continues use; awareness about cancer and its association with tobacco and a lack of it were positively and negatively associated with quitting.…”
Section: Discussionmentioning
confidence: 99%
“…Conlon et al 6 conducted a survey of 493 patients with newly diagnosed HNSCC and a history of smoking, 183 of whom were current smokers. Of the current smokers, 157 (85.8%) were currently 7 found that among active and former smokers with HNSCC, the primary self-reported motivations to quit were perceived benefits of quitting, advice from their physicians, and awareness of the association between tobacco and cancer. The authors also found continued smoking to be associated with coping mechanisms, nihilistic perception of the prospects of their cancer care, and poor understanding of the association of cancer and tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found continued smoking to be associated with coping mechanisms, nihilistic perception of the prospects of their cancer care, and poor understanding of the association of cancer and tobacco. 7 Their findings suggest that smokers with HNSCC are interested in quitting and motivated to quit at the time of diagnosis of HNSCC, most often because they understand the health implications of continuing to smoke. Effects of treatment on the enjoyment or ease of tobacco use are another potential explanation for the higher tobacco use cessation rates in the first 6 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study suggested that even after being diagnosed with Head and Neck Cancer, one third of the study population continued to use tobacco. [ 15 ] Thus, it becomes an integral part of health professionals to provide a structured approach to initiate smoking cessation, manage withdrawal symptoms, and provide long-term support. [ 16 ] However, these cessation programs are usually customised according to individuals.…”
Section: Introductionmentioning
confidence: 99%